Exploring Sustainable Management Practices in the Hospitality Industry: A Qualitative Study - Ruslaini Ruslaini; Yessica Amelia; Eri Kusnanto (LPPM STIE Kasih Bangsa, 2024)
This qualitative study investigates sustainable management practices within the hospitality industry. The research aims to understand the current landscape of sustainability initiatives and their implementation in hospitality establishments. Employing a qualitative approach, semi-structured interviews were conducted with industry experts and managers. Purposive sampling was utilized to select participants with diverse experiences and perspectives. Data analysis followed thematic analysis techniques, identifying key themes and patterns related to sustainable management practices. Results indicate a growing awareness and adoption of sustainability measures in the hospitality sector, including efforts to reduce waste, conserve resources, and engage with local communities. This study contributes to the ongoing discourse on sustainability in hospitality management, providing insights into effective strategies and challenges faced by industry stakeholders